2016
DOI: 10.1080/10942912.2015.1086787
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivities ofAchillea millefoliumEssential Oil and Its Main Terpenes from Iran

Abstract: Achillea millefolium L. comprise several relevant species for the food, cosmetic, perfumery and pharmaceutical industries. Gas chromatography/mass spectrometry analysis revealed borneol to be a major component of A.millefolium, with its contribution to the essential oil (EO) being 36.35%. Borneol exhibited significant lipid peroxidation inhibition and antimicrobial activity against all tested bacterial strains. In addition, borneol had the highest antioxidant activity in all conducted assays. The borneol had s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 34 publications
1
21
0
2
Order By: Relevance
“…Our results showed that the free radical scavenging capacity of the plants harvested in full flowering stage was higher than many Achillea species in previous study. It was determined that some Achillea species showed stronger antioxidant activity than positive controls also at previous studies by researchers, as in our study . Antioxidant activity can be varied in different organs and phenological stages of the same species.…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…Our results showed that the free radical scavenging capacity of the plants harvested in full flowering stage was higher than many Achillea species in previous study. It was determined that some Achillea species showed stronger antioxidant activity than positive controls also at previous studies by researchers, as in our study . Antioxidant activity can be varied in different organs and phenological stages of the same species.…”
Section: Resultssupporting
confidence: 75%
“…There are many reports about the antimicrobial activity of the volatile oils of Achillea species . Kazemi reported that volatile oil of A. millefolium showed higher antimicrobial activity than the control antibiotics against all fungal and bacterial organisms tested ( C. albicans , A. fumigatus , B. cereus , E. faecalis , S. aureus , E. coli , P. aeruginosa , P. mirabilis , S. typhimurium and C. freundii ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[9,10] Phenolic compounds, such as flavonoids and phenolcarbonic acids, constitute one of the most important groups of pharmacologically active components in yarrow. [8,11,12] Recent studies have demonstrated that the Achillea genus possesses antioxidant activity which is pertained to its total phenolic and flavonoid contents. [11][12][13] Also the morphologic and chemical composition of Achillea species was affected by environmental conditions such as plant genetic type, seasonality, cultivar, geographic location, and developmental stage, because of a chemically polymorphic and perennial.…”
Section: Introductionmentioning
confidence: 99%